Middle Meningeal Artery Embolization as Treatment for Chronic Subdural Hematoma: A Case Series. Issue 5 (25th July 2017) - Link, Thomas W; Boddu, Srikanth; Marcus, Joshua; Rapoport, Benjamin I; Lavi, Ehud; Knopman, Jared
Abstract: BACKGROUND: Traditional treatment for symptomatic subdural hematoma (SDH) has been surgical evacuation, but recurrence rates are high and patients often harbor complex medical comorbidities. Growth and recurrence is thought to be due to the highly friable nature of the vascularized membrane that forms after initial injury. There have been reported cases of middle meningeal artery (MMA) embolization for treatment of recurrent SDH after surgical evacuation with the goal of eliminating the arterial supply to this vascularized membrane. OBJECTIVE: To present the first known case series of MMA embolization as upfront treatment for symptomatic chronic SDHs that have failed conservative management in lieu of surgical evacuation. METHODS: Five patients with symptomatic chronic SDHs underwent MMA embolization using PVA microparticles at our institution. Size of SDH was recorded in maximum diameter and total volume. RESULTS: Four patients underwent unilateral and 1 underwent bilateral MMA embolization successfully. All cases had significant reduction in total volume of SDH at longest follow-up scan: 81.4 to 13.8 cc (7 wk), 48.5 to 8.7 cc (3 wk), 31.7 and 88 to 0 and 17 cc (14 wk, bilateral), 79.3 to 24.2 cc (8 wk), and 53.5 to 0 cc (6 wk). All patients had symptomatic relief with no complications. Histologic analysis of the chronic SDH membrane in a separate patient that required surgery revealed rich neovascularization with many capillaries and few small arterioles. CONCLUSION: MMA embolization could present a minimally invasive and low-risk initial treatment alternative to surgery for symptomatic chronic SDH when clinically appropriate.